# math

posted by .

Simplfy.(82-60)+ [(-3 x 4)- 36/4]

• math -

Do what is in parenthesis first. You get
12 + {12 - 36/4}
Next do what is in the brackets
12 - 36/4 = 48/4 - 36/4 = 12/4 = 3 or
12 - 9 = 3 whichever way you prefer.
Then, you are left with 12 - 3
Hope this makes sense!

## Similar Questions

1. ### Math

Simplfy 7sqrt(3/6)
2. ### Math

Simplfy 10^1 x 10 ^-2 x 10 ^-1
3. ### math

d/dx(e2x-3)find indicated derivative and simplfy
4. ### Math

8/2 [2/ 9] how to simplfy above question.
5. ### Math

Expand an simplfy. 3(x-6)(x+4)-(3x-5)^2 Is the answer -6x^2+24x-39
6. ### math

square root of 45 simplfy by factoring
7. ### math

simplfy 3 root 3/8
8. ### Math

Simplfy the following 10.2*1.4/4.8
9. ### math

-12 รท 3 x ( -8 + (-4)^2 - 6 ) + 2 how do you simplfy this expression?
10. ### Math

Solve. (-10x^3+30x-20) / (-5x+5) A) 2x^2-2x+4 B) -2x^2-2x-4 C) -2x^2+2x+4 D) 2x^2+2x-4*** Simplfy x/6x-x^2 A) 1/6-x; where x=0,6 ***** B) 1/6-x ; where x= 6 C) 1/6x ; where x = 0 D) 1/6 Simplfy x-2/x^2+4x-12 A) 1/x+6; where x=-6 B) …

More Similar Questions